The development and implementation of an innovative community-based intervention to strengthen community capacity for HIV prevention and care among Canadians of African Caribbean and Black (ACB) women in Ontario: a research protocol - Josephine Etowa; Notisha Massaquoi; Francisca Omorodion; Danielle Brown-Shreves; Ilene Hyman; Akalewold Gebremeskel; Hugues Loemba; Bishwajit Ghose; Egbe Etowa; Jennifer Rayner; Charles Dabone; Lounanjio Brown O’Sullivan; et al. (Global Public Health)
African, Caribbean, and Black (ACB) women are overrepresented among new HIV diagnoses due to social and structural factors. This study seeks to create, implement, and evaluate a community-based peer-led intervention to improve access to HIV prevention and care for ACB women in Canada. This multisite, five-year project, using community-based participatory research, implementation science and evaluation frameworks, will be implemented in five non-iterative phases. Phase 1: Community and partner engagement; Phase 2: Critical health and racial literacy training curriculum and HIV resource development; Phase 3: Implementation research with first cohort of trained HIV Peer Equity Navigators [PENs] in three sites; Phase 4: Training of second cohort of HIV PENs and program implementation of HIV PEN intervention across Ontario; and Phase 5: Evaluation, knowledge sharing and plans for national scale up. We will use a mixed methods approach, including quantitative and qualitative data, such as surveys and qualitative interviews, to analyze and identify implementation scenarios, changes in improving access, and ensuring equity to HIV prevention and care for ACB women in Ontario, Canada. Evidence on the effectiveness of this innovative, peer-led intervention will be used to inform policies and practice related to HIV prevention and care for ACB women in Canada.